Advances of Molecular Imaging in Epilepsy - Galovic, Marian (Curr Neurol Neurosci Rep, 2016)
Positron emission tomography (PET) is a neuroimaging method that offers insights into the molecular functioning of a human brain. It has been widely used to study metabolic and neurotransmitter abnormalities in people with epilepsy. This article reviews the development of several PET radioligands and their application in studying the molecular mechanisms of epilepsy. Over the last decade, tracers binding to serotonin and γ-aminobutyric acid (GABA) receptors have been used to delineate the location of the epileptic focus. PET studies have examined the role of opioids, cannabinoids, acetylcholine, and dopamine in modulating neuronal hyperexcitability and seizure termination. In vivo analyses of drug transporters, e.g., P-glycoprotein, have increased our understanding of pharmacoresistance that could inform new therapeutic strategies. Finally, PET experiments targeting neuroinflammation and glutamate receptors might guide the development of novel biomarkers of epileptogenesis.